Program Turikale terhadap Perubahan Saturasi Oksigen dan Kecemasan dalam Menghadapi Masa Pandemi COVID-19 - Rosita Passe; Aminuddin Aminuddin; Ayu Lestari; Jumrah Sudirman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of physical exercise on oxygen saturation and anxiety in dealing with the COVID-19 pandemic in the Timbuseng Village community, Takalar Regency. The research design was quasi-experimental with a pretest-posttest design with a control group. The results showed that oxygen saturation with physical activity where p-value = 0.000 <0.05 and anxiety about physical activity where p-value = 0.000 <0.05. In conclusion, there is a significant effect of giving physical exercise intervention on the value of oxygen saturation and anxiety in the Timbuseng village community, Takalar district. Keywords: Anxiety, Physical Exercise, Oxygen Saturation